A Beverage and Photography Workshop at SMK 17 Agustus 1945: Universitas Ciputra Students Social Innovation Project - LEVI, JOAQUIN; RALPH OWEN CHRISTIANTO; IVAN SATRIA WIRANATA; JOHANES MACO POILLOT; MALVIN BARA WIJAYA (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Students at SMK 17 Agustus 1945 Surabaya's hospitality program learned the fundamentals of beverage production. The objective of this program is to deepen participants' knowledge of beverage production, food costing, advertising strategies, and food photography. They will be taken through every step of starting a business, from calculations to sales. The goal of this session is for attendees to obtain an improved understanding of the fundamental stages involved in running a food and beverage business. The main aim of this program is to provide participants with a fresh perspective of the process of doing business in the food and beverage industry, as well as the practical knowledge required to start a culinary enterprise.